Literature Study: The Role Of Accountants In Reporting Environmental, Social, And Governance Information - Yanuar Ramadhan; Yuliana Resca; Saputra Saputra; Wahyu Diana; Syam S. Qamar (International Journal of Social Service and Research, 2023)
The purpose of this study is to get an overview of the role of accountants in terms of existing literature in relation to information related to Environmental Social Governance (ESG). In addition to the role of accountants, the role of the audit committee is also needed as an independent party in order to minimize the opportunities for accountants and management to commit fraud. Methods: The research method in this article is qualitative research with a literature review approach obtained from articles and journals from pre-existing research. Literature review is a form of literature research by reading various types of books, journals, and the like related to the topic of discussion in research to produce a scientific paper, such as research articles, dissertations, theses, and others. Results: Environmental, Social, and Governance (ESG) information disclosure practices are one of the good strategies to implement for companies, because disclosure of this information is needed to shape a company's image. In order to care and increase awareness of the social environment and surrounding governance. This makes Environmental, Social, and Governance (ESG) a tool for companies to gain legitimacy from the community and stakeholders, where it will cause a positive response in the community by giving confidence in the use of company products, and also trust when investing in the company.